THU0335 IS CARDIOVASCULAR RISK IN INFLAMMATORY MYOPATHIES UNDERESTIMATED?. (2nd June 2020) - Lopez, B.; Fuego-Varela, C.; Galloway, J.; Gordon, P.
Abstract : Background: Inflammatory myopathies (IIM) comprise a heterogeneous group of rare connective tissue diseases (CTD) which can occur in any age group and in association with other autoimmune CTD. Extramuscular manifestations, including cardiac involvement, are common and may occur in the absence of muscle symptoms. The link between inflammation and atherosclerosis has been well established in other immune-mediated diseases suggesting that atherosclerosis in these conditions is driven by disease activity rather than traditional cardiovascular (CV) risk factors. Large observational studies have identified atherosclerotic cardiovascular events (CVE) as one of the leading causes in mortality in IIM but to date there are no specific recommendations for patients with IIM beyond the general guidelines for management of CV risk in the general population. A systematic review of the literature available was carried out, identifying six observational studies based on data collected from local or national healthcare databases. All six studies showed an increased incidence of MI and/or stroke compared to the general population, with a suggestion in some of them that this incidence was particularly high in the first few years after disease onset. Objectives: To establish if the incidence of atherosclerotic CVE in an IIM cohort is higher than expected when compared to QRISK2 predicted risk, and if so to determine if this risk is influenced by disease duration, gender, disease phenotype or ethnicity. Methods: Patients referred to the Myositis clinic at King's College Hospital (KCH) were identified, excluding patients with Inclusion Body Myositis, overlap diagnoses with other CTD or prior atherosclerotic CVE. Only patients fulfilling ACR/EULAR criteria for IIM and under follow up at KCH (Denmark Hill site) were included in the study. Retrospective data was gathered by reviewing electronic patient records. Results: 327 patients were identified through the Myositis Departmental database. After applying exclusion criteria the final dataset consisted of 159 patients (114 female, 71.7%), including dermatomyositis (82 patients), polymyositis (49 patients), Clinically Amyopathic Dermatomyositis (7 patients), anti-synthetase syndrome (12 patients) and necrotizing myopathy (9 patients). 81 patients were white (50.9%). Mean age of entry in the study was 49.1 years (SD 15.2) for women and 49.7 years (SD 12.2) for men. The mean follow up time was 2.61 years with a median time of 2.78 years (IQR 1.64-2.85). The mean disease duration was 6.77 years for the whole cohort with a median time of 4.61 years (IQR 2.43-9.07). The incidence rate of atherosclerotic CVE was 16.3/1000 patient-years (95% CI: 8.8-30.3), twice as high as expected by QRISK2. Analysis showed statistical difference with males (RR=6.49, p=0.002) and white patients (RR=5.04, p=0.02) although the statistical significance for white ethnicity was lost after adjusting for age and gender. Statistical analysis showed association between disease duration and higher incidence of atherosclerotic CVE, with a rate reduction of 0.7 per year from disease onset (p=0.01) after adjusting for age and gender. Conclusion: Our results suggest that atherosclerotic cardiovascular risk in inflammatory myopathies is underestimated, particularly early on the disease. Based on our results we would recommend a low threshold for primary prevention of atherosclerosis including the use of statins particularly for the first year after diagnosis. Disclosure of Interests: None declared